2008
DOI: 10.1002/ejic.200800468
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of NiII and PdII Complexes Bearing N,N,S Tridentate Ligands and Their Catalytic Properties for Norbornene Polymerization

Abstract: A series of new N,N,S tridentate nickel(II) complexes [(ArN = CHC 6 H 4 NPh-2-SPh)NiBr] (Ar = 2,6-diisopropylphenyl, 1; Ar = 2,6-dimethylphenyl, 2; Ar = Ph, 3) and palladium(II) complexes [(ArN = CHC 6 H 4 NPh-2-SPh)PdCH 3 ] (Ar = 2,6-diisopropylphenyl, 4; Ar = 2,6-dimethylphenyl, 5; Ar = Ph, 6) were synthesized and characterized. X-ray diffraction analyses of the single-crystal structures revealed that tridentate complexes 1, 2, 4, 5, and 6 featured a distorted square-planar coordination of the central metal.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(15 citation statements)
references
References 77 publications
0
15
0
Order By: Relevance
“…(X = O, S, Se) ligands, and showed that different heteroatoms and substituents can modulate the catalytic properties [29]. Similar sidearm effect has been reported for other catalyst systems including Cr catalysts [30], Ni and palladium catalysts [31][32][33][34], etc. However, the sidearm modification strategy has scarcely been utilized in metal catalyzed ROP of LA [35].…”
Section: Introductionmentioning
confidence: 56%
See 1 more Smart Citation
“…(X = O, S, Se) ligands, and showed that different heteroatoms and substituents can modulate the catalytic properties [29]. Similar sidearm effect has been reported for other catalyst systems including Cr catalysts [30], Ni and palladium catalysts [31][32][33][34], etc. However, the sidearm modification strategy has scarcely been utilized in metal catalyzed ROP of LA [35].…”
Section: Introductionmentioning
confidence: 56%
“…The anilinotropone ligands were prepared using reported procedure via the Pd-catalyzed amination of 2-triflatotropone with the specific aniline at 60-83 % yields (Scheme 3) [34].…”
Section: Synthesis and Characterization Of Anilinotropone Aluminum Comentioning
confidence: 99%
“…However, the examples of nickel complexes bearing tridentate or multidentate ligands used in the vinyl polymerization of norbornene were much less and their catalytic activities were also relatively lower than those of nickel complexes with bidentate ligands. Nickel complexes bearing tridentate ligands, such as phenoxy-imino ligands with an hydroxyl or alkoxyl group sidearm ([ONO]) [38,39], phenoxyl-imino (quinoline) or (imino)pyridyl alcohol ligands ([NNO]) [40,41], bis(imino) pyridine ligands ([NNN]) [42e45], pyrrole-imine ligand with orthoPPh 2 group ([PNN]) [46] and anilidoeimino ligand with a sidearm group containing an S donor atom ([NNS]) [47], have been reported to be used as precatalysts for the vinyl polymerization of norbornene. Very recently, nickel complexes with multidentate ligands, mainly tetradentate [NNNN] ligands [48e51], were reported to afford moderate to high catalytic activities for the vinyl polymerization of norbornene upon activation with MAO or MMAO.…”
Section: Introductionmentioning
confidence: 99%
“…Interest in polymers of cyclic olefins such as norbornene (NB) (bicyclo[2.2.1]hept‐2‐ene) has increased dramatically because of the attractive properties of this addition type of polymer such as high chemical resistance, good UV resistance, low dielectric constant, high glass transition temperature, excellent transparency, large refractive index and low birefringence . Up to now, vinyl‐addition polymerization of norbornene has been reported using many transition metal catalysts, including Ti, Zr, Fe, Ni, Pd, Co, Cu and Cr . Janiak and Bao have given a full literature and patent account on the work describing the addition polymerization of norbornene .…”
Section: Introductionmentioning
confidence: 99%
“…Among these catalysts, late transition metal catalysts (Ni and Pd) exhibited especially high activity . It is known that the polynorbornenes (PNBs) catalyzed by palladium‐based catalysts are usually insoluble in common solvents, whereas those obtained by‐nickel based catalysts are soluble in chlorohydrocarbons . Therefore, nickel‐based catalysts show great potential for application in norbornene homopolymerization.…”
Section: Introductionmentioning
confidence: 99%